PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GALLERY WALK TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP NEGERI 8 PADANGSIDIMPUAN - Adek Nilasari Harahap (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2021)
This study aims to determine (1) the mathematical communication ability of students taught by the gallery walk type cooperative learning model is higher than the mathematical communication skills of students taught by conventional learning models (2) student responses through the application of the gallery walk type cooperative learning model to communication skills. mathematics students of SMP Negeri 8 Padangsidimpuan. The research method used is quasi-experimental. The population of this study were all seventh grade students of SMP Negeri 8 Padangsidimpuan. Sampling using simple random sampling. The sample is class VII-2 as the experimental class and class VII-1 as the control class. Data collection using a mathematical communication ability test sheet.The results showed (1) t_(count )= 3.56 and t_(table )= 1.67 or) t_(count ) > t_(table ) so that it can be concluded that students' mathematical communication skills are taught by cooperative learning model type gallery walk is higher than the mathematical communication ability of students who are taught by conventional learning models. (2) Based on the results of student responses, an average score of 3.55 was obtained so that it can be concluded that student responses through the application of the gallery walk type cooperative learning model to the mathematical communication skills of SMP Negeri 8 Padangsidimpuan students were very positive.